Rule modeling for automatic verification of RDC-50 requirements in EAS - Miyamoto, Vania Furuguem; Pereira, Silvia Maria Soares de Araujo; Menegotto , José Luis (Seven Editora, 2024)
The modeling of rules for the automatic verification of requirements of architectural programs of Health Care Establishments (EAS) represents one of the many challenges related to the adoption of the BIM methodology in the processes of the Coordination of Projects and Works of Cogic-Fiocruz. These programs need to comply with the requirements of RDC-50. With a new process of approval of most of the activities of the EASs in the city of Rio de Janeiro, by the municipal secretariat and no longer by the State Health Surveillance and, when the visa service in plan is terminated by the municipal agency, the possibility and severity of the risk of non-compliance of the EAS already built or in project increases. The objective of this research is to study how to model rules for automatic verification of RDC-50 requirements, in the Solibri Model Checker (SMC) tool, using information from the BIM model of the Germano Sinval Faria School Health Center (CSEGSF), located at the Manguinhos Campus of Fiocruz, in Rio de Janeiro. The research methods used were bibliographic and documentary reviews, as well as exploratory research. In this study, the conditions for achieving the objective are presented, the importance of the organization and the information classification system and the modeling of the rule itself in the SMC, for the automatic verification of the minimum areas of the environments of the CSEGSF BIM model, according to the requirements presented in RDC-50. It also presents a reflection on the parameterization of the requirements of RDC-50 and the construction of domain-specific ontologies for various aspects of the SUS system, with its challenges and difficulties. DOI:https://doi.org/10.56238/sevened2024.025-014